Decovidization through Rurbanization: The Re-development Option for Sustainable Energy Access - Sen, Salil K. (International Journal of Energy Economics and Policy, 2020)
As the energy infrastructure is re-orienting to cater to de-covidization, this paper posits the rurbanization option. De-covidization is defined as actionable options to migrate from the corona virus pandemic, seen through the lens of sustainable energy access. De-covidating would imply ‘build and retrofit-back better’ with respect to energy access. De-covidization has implications on scale, locale, alignment for energy access in the rurbanized format. The locale and reach of rurbanized energy access need to blend with living habitat. This paper is on the construct of de-covidization through grass-roots up energy access options through an innovation, rurbanization. Rurbanization refers to rural-urban aligned resource corridors that offer potential for sustainable energy access. Rurban interface is a metric that assesses the possibility of redesigning and rescaling carbon proof energy access options. There is sparse literature on the concept of rurbanization that hybridizes benefit incidence and network views on urban-rural interfaces. The focus is sustainable energy access. The paper conceptualizes rurbanization to bridge the gap in the research that emanates from the propensity of urban megapolises to create clutter, which results in degraded ecology, air pollution, health hazards, lower quality of life, gender inequity, and vulnerability to natural disasters. This has exacerbated during the current global pandemic. As de-covidating initiatives are unleashed, the energy access would need appropriate and manageable scale. Urbanization cannot be sustained without a robust rural interface. Keywords: Rurbanization, De-covidization, Energy Access, Ecology-driven Shared Value Creation, Water-waste-energy Metrics JEL Classifications: Q01, O35, R580 DOI: https://doi.org/10.32479/ijeep.10239